Hubungan Pola Asuh Demokratis Orang Tua dengan Keberhasilan Prososial Siswa Tuna Grahita Ringan (C) di SLB.C Kemala Bhayangkari 2 Gresik - Nor Afni Aufa Risfi; Muhimmatul Hasanah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2020)
Parenting patterns are very influential as a support for the prosocial success of mild mentally retarded children. Helping behavior, or it can also be called prosocial behavior, is strongly influenced by parenting, which is basically the first social behavior that comes from their parents, because parents are the main and first educators before children receive education in school, because it is from the family that children are born. first time studying. The purpose of this study is to empirically prove whether there is a relationship between democratic parenting of parents and the prosocial success of mild mentally retarded (C) students in special schools. C Kemala Bhayangkari 2 Gresik. The subjects in this study amounted to 27 students with mild mental retardation (C) from a population of 27 students with mild mental retardation. Taking the subject using a saturated sampling technique. Data collection techniques used measuring tools for democratic parenting of parents and measuring tools for prosocial behavior. The research data was then analyzed using the Spearmant Rank correlation technique. The result of this study is that there is a significant positive relationship between parents' democratic parenting and the prosocial behavior of mild mentally retarded (C) students in special schools. C Kemala Bhayangkari 2 Gresik is indicated by the value (r) = 0.779 and (p) = 0.000 (p <0.05).